Perceived and Objective Quality of Life Among Pregnant Women: Mixed-Methods Research on Chronic Energy Deficiency - Fitri Apriyanti; Diah Wulandari; M. Nizar Syarif Hamidi (Jurnal Penelitian Pendidikan IPA, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a substantial public health issue in Indonesia.  This research examines the divergence between objective and subjective quality of life in pregnant women with CED in Kampar District, Riau Province.  A sequential explanatory design with mixed methodologies was used.  The quantitative phase included 150 pregnant women with chronic energy deficiency (mid-upper arm circumference <23.5 cm) from 10 community health centers (out of 31 in Kampar District), selected using a strategy that guarantees a blend of urban and rural regions.  Evaluations included WHOQOL-BREF, anthropometric assessments, and clinical exams.  The qualitative phase included comprehensive interviews and focus group discussions with 30 intentionally chosen individuals.  Data integration was executed by joint display analysis. Quantitative results indicated poor objective quality of life scores: physical domain: 54.3±12.7; psychological: 58.6±11.4; social: 64.2±13.8; environmental: 52.1±10.9.  Nonetheless, 73% of interviewees regarded their quality of life as "good" or "excellent."  Qualitative analysis revealed four themes: "normalization of adversity" (CED seen as typical during pregnancy), "family sacrifice" (prioritization of familial needs), "social support as resilience" (help from family and community), and "spiritual coping" (religious beliefs as a source of strength).  Key determinants affecting the disparity in quality of life were social support (β=0.432, p<0.001), psychological resilience (β=0.387, p<0.001), healthcare access (β=0.256, p<0.05), and health literacy (β=0.198, p<0.05). Despite unfavorable objective health indicators, pregnant women with CED in Kampar District maintain good perspectives of quality of life, facilitated by robust social support, cultural normalization, and spiritual coping strategies.  Effective therapies must amalgamate biological strategies with psychological assistance, taking into account local cultural factors.  Programs must fulfill dietary requirements while concurrently enhancing community support structures and advancing health literacy to reconcile the disparity between objective health status and subjective well-being.